Pengembangan Brownies Zenin Sebagai Pangan Fungsional Berbasis Lokal Untuk Pencegahan Stunting - Gusti Ayu Dewi Kusumayanti; Hijrah Asikin; Nursalim - (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2025)
Stunting remains a major chronic nutritional problem in Indonesia and requires intervention through the provision of supplementary feeding (PMT). This study aimed to develop Zenin Brownies as a functional food based on local ingredients to help prevent stunting. The brownies were formulated by substituting wheat flour with mung bean flour, pumpkin seed flour, Ambon banana, and cashew nuts. The study was conducted experimentally with three treatment formulations (P1, P2, P3), involving organoleptic testing by 30 panelists and laboratory analysis of protein, calcium, and zinc content. The results showed that treatment P2 had the highest acceptance rate (90%) with average scores for color 4.00; aroma 4.00; texture 4.13; taste 4.13; and overall acceptance 4.10. The nutritional content per 100 g of P2 included 13.11 g of protein, 16,926.59 ppm of calcium, and 46.7 ppm of zinc. Meanwhile, per portion (50 g), it contained 174.54 kcal of energy, 6.56 g of protein, 9.59 g of fat, 17.73 g of carbohydrates, and 0.95 g of dietary fiber. P2 was selected as the best formulation due to its favorable sensory attributes, high nutritional value, and potential as an innovative, locally sourced, and nutritious supplementary food product.